Konsep Kebenaran Religius Dalam Filsafat Ilmu Dan Relevansinya Terhadap Penetapan Hukum Islam Kontemporer - Farham .; Ramsiah Tasruddin (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
Discourse on the nature of truth often triggers tension between the positivistic paradigm of Western scholarship and dogmatic religious beliefs. This article aims to analyze the concept of religious truth within the epistemological framework of the philosophy of science and analyze its relevance as a philosophical foundation in contemporary Islamic law-making (istinbath) methodology. Using a qualitative method based on library research, this study combines philosophical and normative-ushuliyah approaches to analyze authoritative texts related to the philosophy of science and the renewal of ushul fiqh. The results show that in Islamic epistemology, revealed (religious) truth and rational-empirical (scientific) truth are complementary. In the context of contemporary ijtihad, establishing law on modern issues (such as bioethics and the digital economy) requires an integration of both. The philosophy of science and knowledge provides empirical data to verify the object of law (tahqiq al-manath), while religious truth acts as an axiological framework that maintains the objectives of sharia (maqasid al-shari'ah). This article concludes that dialogue between scientific and religious truth is absolutely necessary so that Islamic legal products do not become trapped in textual puritanism, but rather remain logical, relevant, and solution-oriented in responding to the challenges of modern civilization.